2012
DOI: 10.1177/1059840512446704
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Related to Suicidal Ideation and Attempted Suicide

Abstract: Suicidal trends and related characteristics such as sociodemographic factors, psychological factors, and health behaviors can differ between countries. This study investigated the predictors of suicidal ideation and attempted suicide including health behaviors among American and Korean youth from two national representative data sets. In both countries, depression was the most predominant predictor to suicidal ideation and attempted suicide. Unique predictors of suicidal youth in each country were also found. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
4
17
0
5
Order By: Relevance
“…This study demonstrated that the degree of depressed mood was another risk factor inducing SI, and that students with a degree of depressed mood were likely to develop SI, regardless of gender. (Chung & Joung, ) discovered that depression is the most predominant predictor of SI and attempted suicide among American and Korean youth based on two national representative datasets . Similar to other reports in the literature on the relationship between depression and suicide, depressed adolescents were also reported to experience frequent occurrences of SI.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that the degree of depressed mood was another risk factor inducing SI, and that students with a degree of depressed mood were likely to develop SI, regardless of gender. (Chung & Joung, ) discovered that depression is the most predominant predictor of SI and attempted suicide among American and Korean youth based on two national representative datasets . Similar to other reports in the literature on the relationship between depression and suicide, depressed adolescents were also reported to experience frequent occurrences of SI.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic factors as religious affiliation and age were also found to have significant individual and interaction effects on college students' suicidal ideation. On independent effect age, past study (Chung, et al, 2012) also reported that age predicted suicidal ideation among American and Korean youths. Similarly, religious affiliation was found to have a significant effect on suicidal ideation among college students.…”
Section: Discussionmentioning
confidence: 88%
“…Noticeably, however, the prevalence of sleep satisfaction among South Korean adolescents was half that of BC Asian adolescents, although the protective relationship with heavy drinking was similar in both groups. South Korean adolescents commonly reduce their hours of sleep to aim for better academic achievement to be admitted to well-known universities, and insufficient sleep is a risk factor for suicidal ideation and suicidal attempts among South Korean adolescents (Chung & Joung, 2012). School nurses could help us to promote student health among both BC Asian adolescents and South Korean adolescents by screening students with sleep problems for alcohol use, educating adolescents about the effects of heavy drinking on effective sleep, and encouraging them to monitor their sleep patterns including sleeping time, hours of sleep, and sleep satisfaction.…”
Section: Shared Risk and Protective Factors For Heavy Drinking Amonmentioning
confidence: 99%